Impact of Short- and Long-term Tai Chi Mind-Body Exercise Training on Cognitive Function in Healthy Adults: Results From a Hybrid Observational Study and Randomized Trial - Walsh, Jacquelyn N. (Glob Adv Health Med, 2015)
BACKGROUND: Cognitive decline amongst older adults is a significant public health concern. There is growing interest in behavioral interventions, including exercise, for improving cognition. Studies to date suggest tai chi (TC) may be a safe and potentially effective exercise for preserving cognitive function with aging; however, its short-term and potential long-term impact on physically active, healthy adults is unclear. OBJECTIVE: To compare differences in cognitive function among long-term TC expert practitioners and age-matched and gender-matched TC-naïve adults and to determine the effects of short-term TC training on measures of cognitive function in healthy, nonsedentary adults. DESIGN: A hybrid design including an observational comparison and a 2-arm randomized clinical trial (RCT) PARTICIPANTS: Healthy, nonsedentary, TC-naive adults (50 y-79 y) and age-matched and gender-matched long-term TC experts METHODS: A cross-sectional comparison of cognitive function in healthy TC-naïve (n=60) and TC expert (24.5 y ÷ 12 y experience; n=27) adults: TC-naïve adults then completed a 6-month, 2-arm, wait-list randomized clinical trial of TC training. Six measures of cognitive function were assessed for both cross-sectional and longitudinal comparisons. RESULTS: TC experts exhibited trends towards better scores on all cognitive measures, significantly so for category fluency (P=.01), as well as a composite z score summarizing all 6 cognitive assessments (P=.03). In contrast, random assignment to 6 months of TC training in TC-naïve adults did not significantly improve any measures of cognitive function. CONCLUSIONS: In healthy nonsedentary adults, long-term TC training may help preserve cognitive function; however, the effect of short-term TC training in healthy adults remains unclear. TRIAL REGISTRATION: ClinicalTrials.gov NCT01340365